Implementasi Pasal 53 Undang-Undang Nomor 22 Tahun 2001 tentang Minyak dan Gas Bumi Terkait Pelaku Usaha Pertamini di Kota Denpasar - Ferdy Pradana; I Nyoman Putu Budiartha; I Wayan Arthanaya (Warmadewa Press, 2021)
Petroleum as a strategic natural resource contained in the Indonesian mining jurisdiction is and has become a national asset that has been controlled by the State. This study aims to explain the legal sanctions for first business actors who trade oil and gas without having a business license to distribute oil and gas and describe the implementation process of the government's prohibition against first business actors in Denpasar. This research uses empirical legal research. The data collection technique was carried out through interviews. The data sources used are primary and secondary legal materials. The results of this study indicate that the regulation regarding legal sanctions for first-time business actors who do not have a license to distribute oil and natural gas has been regulated in Article 53 of Law Number 22 Year 2001 concerning oil and natural gas regarding processing, transportation, storage and commerce. However, with the complexity of business activities today, this regulation has not been able to reach and accommodate the current first developments. The application of the government's prohibition against first business actors in the city of Denpasar is still very contrary to the practice in the field. Only one owner only uses a micro and small business license (IUMK). Apart from that, the government has not been able to take action because there is no legal basis for controlling